Prototipe Antarmuka Dan Basis Data Website Layanan Administrasi Ujian Sekolah - Febria Sri Handayani; Maria Veronica (Jurnal Informatika Global)
The implementation of school exams before the Covid-19 pandemic was carried out with a fairly high intensity of interaction and physical gatherings. After the pandemic hit Indonesia, there were a lot of rules and health protocols that limited the physical gathering activity. This also has an impact on school examination administration services in each educational unit, both in the city and in remote villages. The contribution of this research is to provide a solution to this problem in the form of an integrated administration service website in the network for the implementation of school exams, especially in junior high school education units (SMP). As a first step in this research, a prototype was produced in the form of 10 interface designs and a relational database design for a school exam administration service website named SILADUS. The interface design of this website uses the Human Centered Design (HCD) approach and the Laravel framework, while the database design is based on three levels of database architecture using MySQL as the database management application (DBMS). SILADUS Engineering itself uses the prototype method (prototype), which in its stages supports the design, evaluation, and re-design process repeatedly. The results of this initial design can be continued until the prototyping stage is completed and implemented in the education unit. Keywords : Interface, Database, SILADUS, Covid-19